TEORI DAN KONSEP PERIODISASI PENDIDIKAN ISLAM PADA ANAK USIA BALIGH DALAM PERSPEKTIF AL-QUR’AN - Anas, Anas Nasrudin; Heri, Heri Setiaji; samudi, samudi (Almarhalah: Jurnal Pendidikan Islam, 2025)
Periodization of Islamic education in the Qur'an in children of puberty is intended to foster and develop talent or potential, maintain religious and human values, provide positive and productive provisions, create a generation that has faith and devotion to Allah, improve worship relationships with Allah, fellow humans, and the natural environment. The research aims to study or analyze the periodization of Islamic education in the Qur'an in children of puberty. The research method uses qualitative through library research, the type of data collection uses documentation in the form of books, journals and others, while data analysis uses content analysis. The results of the research findings that the periodization of education for children of baligh age, even though in this phase they have become students or students, but the figure of parents still has a role and is responsible for always the most basic or main educator must continue to be carried out optimally. Therefore, the task of both parents is not only to finance children in formal education, but must continuously carry out guidance and direction as well as good examples to support the success of children in the formal education they are pursuing. Likewise, during the period of puberty, the physical condition of children undergoes many changes, including; growing and developing very quickly, broadening their horizons, becoming strong and hard emotions and starting to awaken their sexual instincts and other changes. Thus, the things that must receive attention from parents and educators, among others, are: Fostering awareness in the child that he has reached the age of adulthood, and providing knowledge related to the law of puberty and teaching related history or stories that can increase devotion, providing encouragement to help with various homework, trying to maximize opportunities and time used for interests and activities that have benefits.